Mexico : In-Firm Training for the Knowledge Economy - Hong Tan (World Bank, Washington, DC, 2014)
The authors use panel firm-level data to study in-firm training in Mexican manufacturing in the 1990s, its determinants, and effects on productivity and wages. Over this decade, not only did the incidence of employer-provided training become more widespread among manufacturing enterprises, but a higher proportion of the workforce received training within firms. Technological change, as proxied by research and development (R&D), was an important driver of these training trends. It contributed to increased training over time through a rising share of firms doing R&D, but more important, through a greater propensity over time to train conditional on conducting R&D. The authors investigate the productivity and wage effects of training in several ways: 1) Estimating the wage and productivity effects of training treated as endogenous. 2) Using training event histories to examine the impact of changing training status over time. 3) Looking at how training (and technology) practices changed where firms were located in productivity and wage distributions over the 1990s. Together, these cross-sectional and panel analyses found evidence that training had large and statistically significant wage and productivity outcomes, that joint training and R&D yielded larger returns than investments in just one or the other, and that both training and technology investments enabled firms to improve their relative position in the wage and productivity distribution between 1993 and 1999.